Evolutionary change in testes tissue composition among experimental populations of house mice. (1st March 2015) - Firman, Renée C.; Garcia‐Gonzalez, Francisco; Thyer, Evan; Wheeler, Samantha; Yamin, Zayaputeri; Yuan, Michael; Simmons, Leigh W.
Abstract: Theory assumes that postcopulatory sexual selection favors increased investment in testes size because greater numbers of sperm within the ejaculate increase the chance of success in sperm competition, and larger testes are able to produce more sperm. However, changes in the organization of the testes tissue may also affect sperm production rates. Indeed, recent comparative analyses suggest that sperm competition selects for greater proportions of sperm‐producing tissue within the testes. Here, we explicitly test this hypothesis using the powerful technique of experimental evolution. We allowed house mice ( Mus domesticus ) to evolve via monogamy or polygamy in six replicate populations across 24 generations. We then used histology and image analysis to quantify the proportion of sperm‐producing tissue (seminiferous tubules) within the testes of males. Our results show that males that had evolved with sperm competition had testes with a higher proportion of seminiferous tubules compared with males that had evolved under monogamy. Previously, it had been shown that males from the polygamous populations produced greater numbers of sperm in the absence of changes in testes size. We thus provide evidence that sperm competition selects for an increase in the density of sperm‐producing tissue, and consequently increased testicular efficiency.